TEACHING DRAWING SCIENCES USING COMPUTER GRAPHICS PROGRAMS - Javahir Makhtumkul ugli Hayitov (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines the features of using information and communication technologies in the educational process. In particular, the possibilities of ICT as a means of increasing the effectiveness of education in the educational process are described.